2017
DOI: 10.1080/1828051x.2017.1291288
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding male and female broiler chickens on low-protein diets fortified with different dietary glycine levels under the hot and humid tropical climate

Abstract: Effects of feeding male and female broiler chickens on low-protein diets fortified with different dietary glycine levels under the hot and humid tropical climate,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 41 publications
6
27
0
1
Order By: Relevance
“…Hot and relatively humid environmental constraint can generate a state of physiological and behavioural stress that might affect the nutrient requirement in broiler chickens which evoke a negative effect on their productive performance, immunity and survivability [ 7 ]. Beneficial use of LP diets with supplemental EAA in a hot-weather has been reported [ 5 , 6 ]. In the present study, despite meeting the requirement for lysine, methionine+cysteine, tryptophan and threonine in LP diets, WG and FCR were depressed throughout the experimental period, regardless of protease supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hot and relatively humid environmental constraint can generate a state of physiological and behavioural stress that might affect the nutrient requirement in broiler chickens which evoke a negative effect on their productive performance, immunity and survivability [ 7 ]. Beneficial use of LP diets with supplemental EAA in a hot-weather has been reported [ 5 , 6 ]. In the present study, despite meeting the requirement for lysine, methionine+cysteine, tryptophan and threonine in LP diets, WG and FCR were depressed throughout the experimental period, regardless of protease supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, despite meeting the requirement for lysine, methionine+cysteine, tryptophan and threonine in LP diets, WG and FCR were depressed throughout the experimental period, regardless of protease supplementation. Reduction of growth performance in broilers fed LP diets and supplemented with EAA has been reported [ 5 ] irrespective of their environmental condition, and this reduction could be associated with lower levels of specific NEAA such as glycine and serine or glutamic acid, or with anon-specific need for nitrogen [ 6 ]. Earlier work on AA-supplemented LP diets in a hot environment [ 5 ] suggested that reduced FI could be a possible explanation for the inferior WG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the beginning of this study sexing was not conducted and, unfortunately, at the end of the study more male chicks were seen in CONT group than in other treatment groups. Note that male chicks generally have higher and lower final BW and FCR, respectively, when compared with female ones [ 19 ]. In Indonesia, the indigenous crossbred chickens are generally produced by the traditional breeders.…”
Section: Discussionmentioning
confidence: 99%
“…Diets reduced in crude protein (CP) or metabolisable energy (ME) have received a lot of attention in poultry nutrition to minimise the feed cost and environmental impact in the past few decades (Rahman et al 2002;Zaman et al 2008). However, reduction of CP and or ME beyond certain levels may exert a negative effect on feed intake (FI) and growth rate (Zaman et al 2008;Dairo et al 2010;Awad et al 2015Awad et al , 2017 broiler chickens may adapt to diet of low-CP or ME content by eating more feed in an attempt to meet their nutrient requirements (Payne 1967;Leeson et al 1996), reduction below a certain level may not be compensated (Attia et al 2011). Moreover, for birds under HS condition, feeding low-CP diets could be detrimental to their feed conversion ratio (FCR) (Zulkifli et al 2018).…”
Section: Introductionmentioning
confidence: 99%